2016
DOI: 10.1007/s00406-016-0733-2
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the association between childhood trauma history and borderline personality disorder or attention deficit/hyperactivity disorder diagnoses in adulthood

Abstract: Common environmental etiological factors between borderline personality disorder (BPD) and attention deficit/hyperactivity disorder (ADHD) have not been fully studied. The main aim of this study was to investigate the relationship between childhood trauma histories, assessed by the Childhood Trauma Questionnaire-Short Form (CTQ-SF), with adult BPD, ADHD or BPD-ADHD diagnoses. Comorbid BPD-ADHD patients exhibited significantly higher clinical severity and higher scores in the Total Neglect Scale, compared to BP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 56 publications
1
29
0
Order By: Relevance
“…Fourth, although the main reason for evaluating only BPD in the present study was that it is the most prevalent personality disorder in both OUD and ADHD patients, not evaluating other personality disorders, which may also be prevalent among these patients is another limitation. Fifth, we did not evaluate traumas, especially interpersonal traumas which are thought to be important in both ADHD and BPD [77,78]. Finally, the generalizability of the findings of the present study to the wider, non-treatment seeking, mixed-gender and homogeneous populations of patients with SUDs requires further study.…”
Section: Discussionmentioning
confidence: 85%
“…Fourth, although the main reason for evaluating only BPD in the present study was that it is the most prevalent personality disorder in both OUD and ADHD patients, not evaluating other personality disorders, which may also be prevalent among these patients is another limitation. Fifth, we did not evaluate traumas, especially interpersonal traumas which are thought to be important in both ADHD and BPD [77,78]. Finally, the generalizability of the findings of the present study to the wider, non-treatment seeking, mixed-gender and homogeneous populations of patients with SUDs requires further study.…”
Section: Discussionmentioning
confidence: 85%
“…For instance, a retrospective study suggested that children who had been maltreated had an increased risk of presenting borderline personality features [47]. Another study in adult reported the association between experiencing traumatic events in childhood and an increased clinical severity of BPD in adulthood [48].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a retrospective study suggested that children who had been maltreated had an increased risk of presenting with borderline personality features [28]. Another study in adult reported the association between experiencing traumatic events in childhood and an increased clinical severity of BPD in adulthood [29]{Ferrer, 2016 #16;Ferrer, 2017 #17}.…”
Section: Discussionmentioning
confidence: 99%